2016
DOI: 10.1007/s11356-016-7719-5
|View full text |Cite
|
Sign up to set email alerts
|

Accelerated eutrophication and toxicity in tropical reservoir water and sediments: an ecotoxicological approach

Abstract: The aim of this study was to jointly show the results of three independent ecotoxicological studies performed to investigate pollutants in three Brazilian tropical reservoirs undergoing accelerated eutrophication. In order to accomplish this goal, the full toxicity identification and evaluation procedure (TIE approach) was performed, at Pampulha (Minas Gerais State) and Salto Grande and Barra Bonita reservoirs (São Paulo State). Acute and chronic toxicity tests were performed using the cladocerans Daphnia simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 88 publications
0
6
0
Order By: Relevance
“…The growth and proliferation of this alga is associated with many complex and synergistic environmental factors, such as climatic variables and nutrients (Muri et al., ; Zeng, Qin, Bao, Li, & Li, ). However, the algae can produce many secondary metabolites, including taste‐ and odor‐causing substances and a family of hepatotoxins called microcystins (Rietzler, Botta, Ribeiro, Rocha, & Fonseca, ). The threat of toxic cyanobacterial blooms in eutrophic waters has raised great concern all over the world in recent decades (Jayme‐Torres & Hansen, ; Smith et al., ; Zeng et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The growth and proliferation of this alga is associated with many complex and synergistic environmental factors, such as climatic variables and nutrients (Muri et al., ; Zeng, Qin, Bao, Li, & Li, ). However, the algae can produce many secondary metabolites, including taste‐ and odor‐causing substances and a family of hepatotoxins called microcystins (Rietzler, Botta, Ribeiro, Rocha, & Fonseca, ). The threat of toxic cyanobacterial blooms in eutrophic waters has raised great concern all over the world in recent decades (Jayme‐Torres & Hansen, ; Smith et al., ; Zeng et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…These reservoirs are located in basins with high level of anthropic impacts, and this directly affects the limnological characteristics of the reservoirs; for example, in Bonita Barra, reservoirs blooms of Microcystis sp and other potentially toxic cyanobacteria are common (Tundisi et al, 2008;Sotero-Santos et al, 2006). The Salto Grande reservoir, located in the central-eastern region of the State of São Paulo, is located in the Atibaia River basin, that has high urban and industrial density (Zanata and Espíndola, 2002), and there are also contributions from several small tributaries draining the urban centers (Rietzler et al, 2018). In the region where Barra Bonita Reservoir is located, there is a strong anthropogenic pressure due to intense industrial activities (Petesse et al, 2007), being considered one of the most populous and industrialized areas in the state of São Paulo (Rietzler et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…The Salto Grande reservoir, located in the central-eastern region of the State of São Paulo, is located in the Atibaia River basin, that has high urban and industrial density (Zanata and Espíndola, 2002), and there are also contributions from several small tributaries draining the urban centers (Rietzler et al, 2018). In the region where Barra Bonita Reservoir is located, there is a strong anthropogenic pressure due to intense industrial activities (Petesse et al, 2007), being considered one of the most populous and industrialized areas in the state of São Paulo (Rietzler et al, 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, the number of publications increased rapidly each year, at an average annual rate of 12.4%, and 252 related publications were published in 2020 (Figure 1). Global warming has severely affected shallow reservoirs, releasing pollutants from sediments and accelerating eutrophication [41,42]. Researchers have found that temperature effects largely determine the distribution of different cyanotoxins in Europe [43].…”
Section: Variation In and Distribution Of The Total Publication Numbermentioning
confidence: 99%